Swelling mechanism of urea cross-linked starchâlignin films in water - Sarwono, A. (Taylor and Francis Ltd., 2018)
Coating fertilizer particles with thin films is a possibility to control fertilizer release rates. It is observed that novel urea cross-linked starchâlignin composite thin films, prepared by solution casting, swell on coming into contact with water due to the increase in volume by water uptake by diffusion. The effect of lignin content, varied from 0 to 20 in steps of 5 at three different temperatures (25Â°C, 35Â°C and 45Â°C), on swelling of the film was investigated. By gravimetric analysis, the equilibrium water uptake and diffusion coefficient decrease with lignin content, indicating that the addition of lignin increases the hydrophobicity of the films. When temperature increases, the diffusion coefficient and the amount of water absorbed tend to increase. Assuming that swelling of the thin film is by water uptake by diffusion, the diffusion coefficient is estimated. The estimated diffusion coefficient decreases from 4.3 to 2.1 Ã 10â7 cm2/s at 25Â°C, from 5.3 to 2.9 Ã 10â7cm2/s at 35Â°C and from 6.2 to 3.8 Ã 10â7 cm2/s at 45Â°C depending on the lignin content. Activation energy for the increase in diffusion coefficient with temperature is observed to be 16.55 kJ/mol. An empirical model of water uptake as a function of percentage of lignin and temperature was also developed based on Fickâs law. Â© 2017 Informa UK Limited, trading as Taylor & Francis Group.